The experiences of bereavement among students following the death of a parent(s) during the semester: the case of students at Midlands State University - Dewah, Milcent Vongai (Midlands State University, 2018)
This dissertation sought to examine the psychosocial effects of bereavement among students who experienced the death of a parent(s) during the semester. The researcher observed that no attention has been given to the grieving University population in Africa but rather attention was given to the children and adolescents. It is only after a student is diagnosed with a bereavement related illness when action is taken. The study was guided by a qualitative approach, through Phenomenological design, which was employed to address the experiences of bereavement following the death of a parent(s) during the semester among students at M.S.U. Heterogeneous purposive sampling was used as a sampling method to select the number of students. Data was analyzed using thematic data analysis. Evidence from the research indicates that the emotional reactions exhibited by the participants included denial, shock, sadness, guilt and regret. The social effects which were faced by the participants were both negative and positive. The negative effects included social alienation, social ills, bravery expected by the community, hopelessness sand family dynamics. The positive social effects included hopefulness, better understanding of death and unity within the family. The coping strategies used by the participants included writing, reading, crying, physical activity, social support, spirituality, sense of humour, counselling, sleeping, graveyard visits, substance use and listening to music. Conclusively, the research brought out the emotional reactions which were exhibited by the participants, social effects experienced by the students and also some unique coping strategies like sleeping which reported to be positive to the participants. The researcher recommended that the Midlands State University should have awareness programs so as to proactively address grief through education among students and also establish on campus and off campus systems to support the bereaving students.